Enhancing the Process of AES: A Lightweight Cryptography Algorithm AES for Ad-hoc Environments - Alharith A. Abdullah; Çağatay Aydin; Oğuz Ata; Mustafa Alhandhal (Journal of Advanced Research in Natural and Applied Sciences)
Ad hoc networks have become more widespread and important because they support mobility and can be used in different situations and some difficult areas such as rescue missions, military, and vehicular communications. Security is stated among the most significant challenges facing Ad Hoc networks due to its characteristic features such as the topology dynamicity, lack of infrastructure centralization, and open architecture. Ad hoc networks work on battery power, and this kind of networks tend to consume more power and time to process data and memory resources through data encryption, eventually requiring a higher amount of power and more time. Therefore, an AES lightweight algorithm is proposed, which is one of the complicated encryption algorithms. This algorithm will be modified to improve the security as well as reduce the amount of time and energy consumed in comparison with the original algorithm. The enhanced version is based on the outputs of sub byte and shift row, in addition to an exclusive X-OR operator between them, whereby the output of the X-OR operator is added to the round key layer. The results confirm that this enhanced algorithm is efficient, accurate, and robust against multiple types of attacks related to ad hoc networks.